Staging International Theatre Festivals in Mid-Pandemic Russia: An Interview with Roman Dolzhanskiy. Issue 3 (2nd October 2022) - Rowson, James
Abstract: Roman Dolzhanskiy speaks to James Rowson about the challenges of organising international theatre festivals in Russia during the COVID-19 pandemic and discusses how the New European Theatre (NET) Festival and Territory Festival have navigated the complex and frequently changing public safety restrictions in Russia.